Structural Complexity and Benthic Cover Explain Reef-Scale Variability of Fish Assemblages in Los Roques National Park, Venezuela - Agudo-Adriani, Esteban A.; Cappelletto, José; Cavada-Blanco, Francoise; Cróquer, Aldo (Frontiers in Marine Science, 2019)
Global and local stressors are causing the worldwide loss of coral cover and structural complexity at an unprecedented pace on reefs. In consequence the habitat of coral reef fish has suffered a profound degradation affecting the abundance, biodiversity and species composition of this taxonomic group. Thus, understanding the link between coral reef fish assemblages and their habitats is paramount to predict their responses to increasing human threats. Herein, we implemented Structure from Motion (SfM) techniques and digital mosaics to characterize the habitat of reef fish in terms of structural complexity and cover of benthic organisms, and we examined the relationships between these metrics and the variation in fish assemblages among sites using a multivariate approach. We found that fish assemblage attributes varied across reef sites in Los Roques, depending on the highly specific features of the benthic habitat. Results indicate that 69% of the variation in species-specific abundance of fish (i.e., reef fish assemblage structure) was explained by cover of massive coral and turf algae, the number and sizes of holes, and the site. Furthermore, when fish biomass per species was utilized as a response variable, 64% of the variation in assemblage structures was explained by a model that included: cover of crustose coralline algae (CCA), variation and the maximum height of reef structures along the transect, the number of holes and the site. All these variables together also explained > 60% of variation of total abundance, biomass and species richness. When data were sorted by trophic groups, CCA cover explained 70% of the variation in forager biomass, whereas the number of holes explained up to 60% of variation in carnivore biomass. These results suggest that each trophic group relates differently to the benthic habitat. We conclude that variation in fish assemblages among sites can be explained by features of the benthic habitat, but more importantly the absence of specific attributes may impact fish trophic groups differently.